(UN)RECONCILED SELVES: AMERICAN BORN CHINESE THROUGH THE LENS OF DU BOISIAN THOUGHT - Almeida, Maria Inês Caldeira de (Inventário, 2020)
Gene Luen Yang’s graphic novel, American Born Chinese, has entered the syllabus of several North American classrooms as a starting point for discussions on racial stereotyping and identity formation. Despite having been compared to how African American authors explore the consequences of negative stereotyping, critics of Yang’s work have directed their attention mostly towards the reality of members from the Asian American community. Yet, this article aims at comprehending how the concepts of “double consciousness” and “two-ness” developed by W.E.B. Du Bois in The Souls of Black Folk (1903) can be used in order to better understand the experience of contemporary Chinese American youths as it has been represented in American Born Chinese. By utilizing Du Bois’s understanding of the psychological impacts of negative stereotyping on his black subjects this work argues that a parallel can be drawn between this African American author’s theory of split consciousness, together with its resulting feeling of otherness, and several narrative elements of Yang’s graphic novel, as well as its tripartite structure. Furthermore, it also examines how both authors present their readers with similar solutions in order for conflicting selves to achieve a state of undivided self-consciousness.